Biological Basis for Cerebral Dysfunction in Schizophrenia in Contrast with Alzheimer’s Disease - Kuljiš, Rodrigo O.; Colom, Luis V.; Rojo, Leonel E (Frontiers in Psychiatry, 2014)
Schizophrenia and Alzheimer’s disease are two disorders that, while conceptualized as pathophysiologically and clinically distinct, cause substantial cognitive and behavioral impairment worldwide, and target apparently similar — or nearby — circuitry in regions such as the temporal and frontal lobes. We review the salient differences and similarities from selected historical, nosological and putative mechanistic viewpoints, as a means to help both clinicians and researchers gain a better insight into these intriguing disorders, for which over a century of research and decades of translational development was needed to begin yielding treatments that are objectively effective, but still very far from entirely satisfactory. Ongoing comparison and “cross-pollination” among these approaches to disorders that produce similar deficits is likely to continue improving both our insight into the mechanisms at play, and the development of biotechnological approaches to tackle both conditions — and related disorders — more rapidly and efficaciously.